Patients with Russell’s Viper Bite in Praphutthabat Hospital 2006 - 2008 - ชูเกียรติศิริ จินตนา (Disease Control Journal, 2009)
The objective of this study was to review the medical records of Russell’s viper bite patients admitted at Praphutthabat hospital. This retrospective study reviewed the medical records of Russell’s viper bite patients during January 2005 to December 2008. All of the cases studied confirmed diagnosis by finding fang mark and carried the snake to hospital or saw the snake clearly. There were forty-seven patients admitted in Praphutthabat hospital during the study period. Most of them (76.6%) were men, 40.2 years old in mean age. Thirty-two patients (68.1%) arrived at hospital within one hour. Abnormal venous clotting time occurred in thirty-one patients (65.9%). Most of the patients who had local swelling, bleb or gangrene at the bitten sites had abnormal VCT with statistically significant. Five patients (10.6%) had renal failure and one of them need peritoneal dialysis. The patients received purified antivenom 3.1 in mean doses. No patient died. Mean length of hospital stay was 2.94 day. Conclusion: In this study, the Russell’s viper bite patients who had abnormal venous clotting time were treated by antivenom and had good outcome.